2017
DOI: 10.1080/15412555.2017.1304533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pressure Support Ventilation May Be Lost at High Exercise Intensities in People with COPD

Abstract: Pressure support ventilation (PSV) may be used for exercise training in chronic obstructive pulmonary disease (COPD), but its acute effect on maximum exercise capacity is not fully known. The objective of this study was to evaluate the effect of 10 cm HO PSV and a fixed PSV level titrated to patient comfort at rest on maximum exercise workload (WLmax), breathing pattern and metabolic parameters during a symptom-limited incremental bicycle test in individuals with COPD. Eleven individuals with COPD (forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 43 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…These observations extend those from a previous study which also found markers of technological limitation during exercise in COPD patients, even though an intensive care unit ventilator was used [13]. This supports the idea that the ventilator was not able to maintain even the low pressure support used in the present study (although low, Pinspi decreased all along the exercise while the maximal flow generating capacity of the ventilator was reached), therefore it is unlikely that a higher pressure support could have been reached.…”
Section: Oronasal Interfacesupporting
confidence: 89%
See 2 more Smart Citations
“…These observations extend those from a previous study which also found markers of technological limitation during exercise in COPD patients, even though an intensive care unit ventilator was used [13]. This supports the idea that the ventilator was not able to maintain even the low pressure support used in the present study (although low, Pinspi decreased all along the exercise while the maximal flow generating capacity of the ventilator was reached), therefore it is unlikely that a higher pressure support could have been reached.…”
Section: Oronasal Interfacesupporting
confidence: 89%
“…Although some other studies suggest the use of the highest tolerable inspiratory support [37], the median support was only 8 cmH2O in the present study and higher levels were not tolerated by these patients who were naive to NIV. However, it was within the ranges of those used in studies that found that NIV improved endurance capacity [19,20] and matched with the level of pressure support titrated to comfort used in Anekwe et al [13]. Based on the available evidence, we included patients with severe obstruction and ventilatory limitation [7,8,38] and did not include those patients who were eligible to home NIV to prevent bias relating to experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lins et al found swimming to increase the heart rate significantly compared to heart rate at rest (Δ24 beats per minute, p < 0.01), and Anekwe et al found COPD patients who walked with activator poles to have a higher mean heart rate when compared to walking without poles (p = 0.002). 54,56 Belardinelli et al did not find a significant difference in the mean heart rate when comparing dance to supervised exercise training (p = 0.59), although both could be deemed high intensity, given both dance and training groups reported a mean beat per minute over 110. 44 Six studies reported the maximum heart rate as a measure of intensity (n = 342), three of which (Nordic walking and dance) 45,49,55 report that patients 1618 Clinical Rehabilitation 37 (12) achieved pre-set goals for the max heart rate, set at 70-75% of the predicted max heart rate.…”
Section: Quantitative Evidencementioning
confidence: 96%
“…45,47,52 MacBean et al (dance) was the only study to consider perceived intensity, discovering that participants underestimated class duration by up to 15%. 55 Breathlessness-related outcomes were assessed across six studies (four Nordic walking, 45,53,56,57 two dance; n = 132) 30,55 using the Medical Research Council Dyspnoea Scale (p < 0.05), 53 dyspnoea numeric rating scales (p < 0.01 45 ; range of 4-9 out of 10 55 ; non-significant difference to no-pole walkers), 56 lung capacity (Δ7-14%; p < 0.05), 57 and the COPD Assessment Tool (Δ−0.5). 30 Improvements in exercise performance were evaluated across four studies (Nordic walking, skiing, and mixed-sports, n = 350).…”
Section: Quantitative Evidencementioning
confidence: 99%